CREOLIZED TEXTS AS A MEANS OF DEVELOPING LINGUISTIC COMPETENCE OF STUDENTS WITH NON-LINGUISTIC SPECIALTIES (ILMIY TADQIQOTLAR VA YANGI OLAM, 2026)
Abstract: The relevance of using creolized texts in foreign language teaching lies in the need to expand the content and teaching tools through the limitless information potential of these materials. The purpose of this article is to evaluate the effectiveness of creolized texts as a means of developing linguistic competence in students majoring in non-linguistic fields.